1984
DOI: 10.1016/0079-6611(84)90004-1
|View full text |Cite
|
Sign up to set email alerts
|

An offshore eddy in the California current system Part I: Interior dynamics

Abstract: --From January 9 to 17, 1981, detailed observations of the horizontal and vertical structure beneath one of the quasi-permanent semi-stationary mesoscale offshore eddy signatures in the California Current System (CCS) discussed by Bernstein, Breaker and Whritner (1977), Burkov andPavlova (1980), andSimpson (1982) were made. The vertical sections of temperature and density show the presence of a three-layer system. A subsurface warm-core eddy, whose diameter is about 150 km at the 7°C isotherm, is the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 49 publications
(119 reference statements)
5
44
0
Order By: Relevance
“…For the PCUS and the CALUS in the Pacific basin, the observed eddy-types were close to those previously documented. In both of these upwelling systems, the presence of strong subsurface-intensified anticyclones, carrying warm and salty water from their nearcoastal poleward undercurrents, are well sampled by the Argo floats and match the previous observations [Simpson et al, 1984;Johnson and McTaggart, 2010;Chaigneau et al, 2011;Kurian et al, 2011;Colas et al, 2012;Collins et al, 2013]. However, we also highlighted the presence of weak surface-intensified anticyclones in the PCUS that represent 45% of the sampled eddies.…”
Section: Pacific and Atlantic Ebus: Differences Between Their Respectsupporting
confidence: 87%
See 2 more Smart Citations
“…For the PCUS and the CALUS in the Pacific basin, the observed eddy-types were close to those previously documented. In both of these upwelling systems, the presence of strong subsurface-intensified anticyclones, carrying warm and salty water from their nearcoastal poleward undercurrents, are well sampled by the Argo floats and match the previous observations [Simpson et al, 1984;Johnson and McTaggart, 2010;Chaigneau et al, 2011;Kurian et al, 2011;Colas et al, 2012;Collins et al, 2013]. However, we also highlighted the presence of weak surface-intensified anticyclones in the PCUS that represent 45% of the sampled eddies.…”
Section: Pacific and Atlantic Ebus: Differences Between Their Respectsupporting
confidence: 87%
“…These sites have been previously recognized as hot spots for eddy generation [Chaigneau et al, 2009;Kurian et al, 2011]. The observed negative S 0 (Figure 8c) is probably due to the local eddy-induced downwelling of the surface layers composed of fresh Pacific Subarctic Water [Simpson et al, 1984;Emery and Meincke, 1986;Huyer et al, 1991;Checkley and Barth, 2009;Dong et al, 2012] that can be clearly identified in Figure 9a (color shading). The temporal evolution of the corresponding composite anomalies is consistent with their mean profiles and their intensity does not present strong variations between the growth, mature and decay phases (Figures 10a-10c).…”
Section: California Upwelling System (Calus)mentioning
confidence: 61%
See 1 more Smart Citation
“…2) indicates a surface mixed layer down to -20-30 m, which was typical over the course of the cruise. The studied area is close to the western boundary of the California Current System, which can be divided into surface and subsurface waters typically at -200-m depth by characteristic constituent water masses (Simpson et al 1984 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…5-8) contain surface signatures of cold filaments and mesoscale eddies. Complex mixing of inshore and oceanic waters occurs in the transition zone as evidenced by water property distributions (e.g., Simpson et al, 1984;Simpson and Lynn, 1990), as well as chemical distributions (Simpson, 1984) and biological populations (Haury, 1984). Visual interpretation and quantification of thermal fronts in such imagery, however, is difficult because of the overall complexity of the California Current system.…”
Section: Descriptive Synthesismentioning
confidence: 99%